Religion, migration, and identity : methodological and theological explorations - Frederiks, Martha Theodora, 1965- (Theology and Mission in World Christianity, 2016)
Migration has become a major concern. The increase in migration in the 20th and 21st centuries has social, political and economic implications, but also effectuates change in the religious landscape, in religious beliefs and practices and in the way people understand themselves, each other and the world around them. In Religion, Migration and Identity scholars from various disciplines explore issues related to identity and religion, that people - individually and communally -, encounter when affected by migration dynamics. The volume foregrounds methodology in its exploration of the juxtaposition of religion, migration and identity and addresses questions which originate in various geographical locations, demonstrates new modes of interconnectedness, and thus aims to contribute to the ongoing academic discussions on mission, theology and the Christian tradition in general, in a worldwide perspective.